Implementasi Pembelajaran Kurikulum Merdeka Belajar dalam Meningkatkan Nilai Spiritual Siswa - Laely Nur Rohmah; Siti Fatimah; Oky Ristya Trisnawati (Tarbi: Jurnal Ilmiah Mahasiswa, 2023)
This research focuses on increasing students' spiritual values ​​through independent learning curriculum learning. This research aims to find out how to increase spiritual values ​​through independent learning curriculum learning. Uu research uses qualitative methods with a village deskrupul approach used, namely case studies According to Susilo Bahardio and Gudnanto (2011) explained that case study research material is a set method for understanding individual bees in depth by studying it in an integrative and comprehensive manner. So the u method is very suitable for use in this research. aika with a different curriculum than before. The curriculum used after the pandemic was over, namely using the independent learning curriculum. Data collection was used primary and secondary. Primary sources such as observations and interviews, while secondary sources by looking in journals and scientific articles Subject targets on research involving teachers and systems In this curriculum, PAI teachers can improve children's spiritual education through assessments available in the cocideka curriculum. others, namely cognitive and psychomotor assessment